PENGARUH PEMBERIAN TABLET FE DENGAN PERASAN AIR JERUK TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL DI PUSKESMAS SIDOMULYO RI KOTA PEKANBARU - Diana Rifka Yulia Wahyuni; Aninditya Azis; Zulfa Nur Azizah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Pregnancy is something that a woman will experience in her life cycle during reproduction, where a woman has a growing fetus in her vagina. The total maternal mortality rate (MMR) based on the 2017 Indonesian Demographic and Health Survey (SDKI) is 305 per 100,000 live births. The biggest cause of AKI is bleeding, where one of the factors causing the bleeding is anemia. One of the government's mainstay programs in the prevalence of anemia in pregnant women is the distribution of Fe tablets and consuming vitamins including vitamin C contained in citrus fruits.Keywords: Anemia, Citrus Fruits